No Acute Effect of Reduced-exertion High-intensity Interval Training (REHIT) on Insulin Sensitivity - Metcalfe, R.; Fawkner, S.; Vollaard, N. (International Journal of Sports Medicine, 2016)
We have previously demonstrated that reduced-exertion high-intensity interval training (REHIT), requiring a maximum of two 20-s all-out cycling sprints in a 10-min exercise session, improves insulin sensitivity in sedentary men over a 6-week training intervention. However, the acute effects of REHIT on insulin sensitivity have not previously been described. In this study 14 men and women (mean±SD age: 23±5 years; BMI 22.7±4.7 kg·m−2; +˙VO2max: 37.4±8.6 mL·kg−1·min−1) underwent oral glucose tolerance testing 14–16 h after an acute bout of reduced-exertion high-intensity interval training (2×20-s all-out sprints; REHIT), moderate-vigorous aerobic exercise (45 min at ~75% VO2max; AER), and a resting control condition (REST). Neither REHIT nor AER was associated with significant changes in glucose AUC (REHIT 609±98 vs. AER 651±85 vs. REST 641±126 mmol·l−1·120 min), insulin AUC (REHIT 30.9±15.4 vs. AER 31.4±13.0 vs. REST 35.0±18.5 nmol·l−1·120 min) or insulin sensitivity estimated by the Cederholm index (REHIT 86±20 vs. AER 79±13 vs. REST 82±24 mg·l2·mmol−1·mU−1·min−1). These data suggest that improvements in insulin sensitivity following a chronic REHIT intervention are the result of training adaptations rather than acute effects of the last exercise session.
Keywords: high-intensity interval training; acute exercise; insulin sensitivity; sprint interval training; glucose tolerance; time efficient